Identificación de aspectos ambientales significativos del área de Perforación Profunda del Centro Servicio Recursos Geotérmicos del Instituto Costarricense de Electricidad, Guanacaste, Costa Rica - Porras-Barquero, Wendy (Instituto Tecnológico de Costa Rica, 2015)
The activities that allow the operation of the Deep Drilling Geothermal Resources Service Center Area inevitably generate; environmental aspects (EA), as well as, significant environmental aspects (SEA); which produce negative impacts on the environment and the people near the project. The lack of knowledge of these issues by the company, was the reason why field visits took place for three months, to know in detail how works each of the processes on that department. Subsequently, all the acquired knowledge was reflected in the execution of flowcharts and through these, easily they identified, 28 EA,that are relating to the activities of the different processes that deep drilling area has. Once identified the EA, an 2 evaluation was carried out, with a criteria significance matrix and an evaluation of legislation compliance matrix. It resulted in the existence of 5 SEAs; water consumption, the dust particles generation in suspension (cement and esferilita), cement effluent generation, the diesel consumption and its use and the noise emission. To eliminate or minimize the environmental impacts produced by the SEAs, that do not have control measures, the establishment of measures of technology, feasible and efficient control was proposed, these proposals are backed with the technical staff criteria, ensuring, it can be achieved efficiently the reduction of the environmental impacts generated by the company.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2015.
Keywords: Centro servicio recursos geotérmicos; Energía geotérmica; Pozos de perforación; Impacto ambiental